Direct and indirect implications of the COVID-19 pandemic on Amazon's financial situation - Zixuan Qin; Abeer Hassan; Mahalaxmi Adhikariparajuli (Journal of Risk and Financial Management, 2022)
We provide theoretical and empirical insights into the impact of COVID-19 on Amazon's financial position. A longitudinal case study of Amazon's financial situation during the 2016-2020 period, and time-series analysis, ratio analysis, and DuPont analysis, are employed as a quantitative methodology to explore Amazon's financial situation changes before and after the COVID-19 pandemic. As for the robustness of the in-depth analysis, we compare Amazon's financial performance and position with Walmart. The result shows that the COVID-19 pandemic did not have a huge negative impact on the companies' financial performance because of its promotion of their development. However, this study provides an in-depth analysis of the influence of COVID-19 on Amazon's financial situation, which financial aspects are most affected by COVID-19, which are not, and the company's response to COVID-19. Therefore, this study sheds light on the accounting literature to demonstrate the impact of COVID-19 on Internet companies' financial performance and provides some reference values for subsequent academic research.
Keywords: 650; COVID-19; Amazon; DuPont analysis; financial statement analysis